1999
DOI: 10.1541/ieejfms1990.119.1_75
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties and Viscosity of High Temperature Argon Mixed with Iron Vapor

Abstract: Thermodynamicproperties such as enthalpy and specific heat, and viscosity of different compositions of argon-iron mixture gases are calculated under the assumption of local thermal equilibrium for a temperature range of 2,500K to 30,000K.The enthalpy decreases basically with increasing iron vapor content, however increases in the temperature range between 5,000 and 14,000K due to the ionization of iron atoms around 7,000K. The specific heat changes complexly with temperature having several peaks corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 1 publication
4
7
0
Order By: Relevance
“…The viscosity and the thermal conductivity coefficients of iron vapour were taken from [9]. Although the Wilke estimation is not very accurate for plasma it has been found that in our case the values obtained by Fluent are in fair agreement with the values obtained from more rigorous calculations [10]. Similar agreement has been found in the case of thermodynamic properties.…”
Section: Modellingsupporting
confidence: 83%
“…The viscosity and the thermal conductivity coefficients of iron vapour were taken from [9]. Although the Wilke estimation is not very accurate for plasma it has been found that in our case the values obtained by Fluent are in fair agreement with the values obtained from more rigorous calculations [10]. Similar agreement has been found in the case of thermodynamic properties.…”
Section: Modellingsupporting
confidence: 83%
“…The validity of the calculation methods and the average cross sections regarding Ar has already been confirmed through the comparison of our results on the electrical and thermal conductivity and viscosity of pure Ar with the reported values of calculation and experiment [11,12]. But in the present paper, we used the rigid sphere model for some interactions.…”
Section: Validity Of the Methodssupporting
confidence: 62%
“…The validity of the method has already been confirmed by comparison of reported results on the specific enthalpy and specific heat of pure Ar and our calculation results [11]. Also, we used all possible new data on molecular constants.…”
Section: Calculation Methods and Its Validitysupporting
confidence: 59%
See 1 more Smart Citation
“…The calculation method was the same as that used in [5] and [7] and an outline of the method is provided in an appendix to this paper. The particle composition of high-temperature air contaminated with copper vapour (0.1 MPa) was obtained from [10]. Figure 5 shows the calculated results of the particle composition [10].…”
Section: Results Of Calculating the Self Absorption Of The Spectral L...mentioning
confidence: 99%